UJI KELAYAKAN BATU PECAH DESA PARIDA KECAMATAN LASALEPA KABUPATEN MUNA SEBAGAI AGREGAT KASAR CAMPURAN BETON - Irvan Jaya; Romy S. E. Tamburaka; Wayan Mustika (PRODI D3 TEKNIK SIPIL, 2020)
Abstract In Muna Regency, there are some kinds of mountain rocks, including in Parida Village, Lasalepa District. There is a place where local people usually take crushed stone to be used as a material for making concrete. The area of land where the local people used to collect mountain stones was ± 2 hectares. Based on the description, the writer considers it necessary to conduct research in order to complete the final project by taking the title